Immunomodulating phytochemicals: an insight into their potential use in cytokine storm situations - Alarabei, Abdusalam Abdullah; Abd Aziz, Nur Aimi Liyana; Ab Razak, Nur Izah; Abas, Razif; Bahari, Hasnah; Abdullah, Maizaton Atmadini; Hussain, Mohd Khairi; Abdul Majid, Amin Malik Shah; Basir, Rusliza (Tabriz University of Medical Sciences and Health Services, 2023)
Phytochemicals are compounds found in plants that possess a variety of bioactive properties, including antioxidant and immunomodulatory properties. Recent studies have highlighted the potential of phytochemicals in targeting specific signalling pathways involved in cytokine storm, a life-threatening clinical condition resulting from excessive immune cell activation and oversupply of proinflammatory cytokines. Several studies have documented the immunomodulatory effects of phytochemicals on immune function, including their ability to regulate essential cellular and molecular interactions of immune system cells. This makes them a promising alternative for cytokine storm management, especially when combined with existing chemotherapies. Furthermore, phytochemicals have been found to target multiple signalling pathways, including the TNF-±/NF-ºB, IL-1/NF-ºB, IFN-³/JAK/STAT, and IL-6/JAK-STAT. These pathways play critical roles in the development and progression of cytokine storm, and targeting them with phytochemicals represents a promising strategy for controlling cytokine release and the subsequent inflammation. Studies have also investigated certain families of plant-related constituents and their potential immunomodulatory actions. In vivo and in vitro studies have reported the immunomodulatory effects of phytochemicals, which provide viable alternatives in the management of cytokine storm syndrome. The collective data from previous studies suggest that phytochemicals represent a potentially functional source of cytokine storm treatment and promote further exploration of these compounds as immunomodulatory agents for suppressing specific signalling cascade responses. Overall, the previous research findings support the use of phytochemicals as a complementary approach in managing cytokine storm and improving patient outcomes.